Earthworm species in no-tillage agroecosystems and native Atlantic forests in Western Paraná, Brazil - Santos, Alessandra; Gorte, Tatiane; Demetrio, Wilian C.; Ferreira, Talita; Nadolny, Herlon; Cardoso, Guilherme B.x.; Tonetti, Caroline; Ralisch, Ricardo; Nunes, Amanda P.; Coqueiro, Ana Carolina P.; Leandro, Hudson C.l.; Wandscheer, Cassio A.r.; et al. (Zootaxa, 2018)
Earthworm populations often increase with the adoption of no-tillage (NT) practices, but few studies have evaluated earthworm diversity in these agroecosystems. In the present study we assessed earthworm species richness in 40 sites under NT and six native Atlantic forest fragments in Western Paraná, Southern Brazil. At each site earthworms were sampled quantitatively (n=5) and qualitatively (n=5), by handsorting soil monoliths (20 x 20 cm width x 20 cm depth), totaling 460 samples overall. Earthworms were killed and fixed in 96% ethanol, counted and identified. Overall, 18 species were found, in the families Acanthodrilidae, Glossoscolecidae, Megascolecidae, Rhinodrilidae and Ocnerodrilidae, of which 10 were native and eight exotic. No-tillage agroecosystems had larger earthworm populations and higher species richness overall than native forests, although this was mainly due to colonization of these agricultural fields by exotic species. Mostly native species were found in the Atlantic forests, highlighting the importance of these habitats as refugia for native earthworm species conservation.